Application of the Team Emergency Assessment Measure Scale in undergraduate medical students and interprofessional clinical teams: validity evidence of a Spanish version applied in Chile - Armijo-Rivera, Soledad; Ferrada-Rivera, Sandra; Aliaga-Toledo, Marcela; Pérez, Leonardo A. (Frontiers in Medicine, 2023)
Background Teamwork is one of the competencies necessary for physicians to work effectively in health systems and is a competency that can be developed with simulation in professionals and medicine students. The Team Emergency Assessment Measurement (TEAM) was created to evaluate the non-technical performance of team members during resuscitation events in real teams. The TEAM scale includes items to assess leadership, teamwork, situational awareness, and task management. An objective evaluation tool in Spanish is valuable for training health professionals at all undergraduate and continuing education levels. This study aimed to generate evidence of the validity of the Team Emergency Assessment Measure (TEAM) in Spanish to measure the performance of medical students and adult, pediatric, and obstetric emergency clinical teams in simulated emergencies as a self-assessment tool. Methods To develop the Spanish version of the instrument, a forward and backward translation process was followed by independent translators, native and fluent in English and Spanish, and a review by a panel of Chilean experts comprising three trained simulation instructors to verify semantics and cultural equivalence. High-fidelity simulations with debriefing were conducted with 5th-year medical students, in which students and instructors applied the Spanish version of the TEAM scale. In the second stage, adult, pediatric, and obstetric emergency management simulations were conducted using the TEAM scale for real clinical teams as a self-assessment tool. Findings By applying the overall TEAM scale to medicine students and clinical teams, Cronbach's alpha was 0.921. For medical students' self-assessment, we obtained Cronbach's alpha of 0.869. No significant differences were found between the overall scores and the scores by dimensions evaluated by instructors and students (p > 0.05). In the case of clinical team training, Cronbach's alpha was 0.755 for adult emergency teams, 0.797 for pediatric emergency teams, and 0.853 for obstetric emergency teams. Conclusion The validated instrument is adequate for evaluating teamwork in medical student simulations by instructors and peers and for self-assessment in adult, pediatric, and obstetric emergency clinical teams.